1981
DOI: 10.1111/j.1365-2621.1981.tb04929.x
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study of the Loss of Vitamin C, Color, and Firmness During Thermal Processing of Canned Peas

Abstract: The kinetic parametc:rs, D and z, for the loss of color, firmness, and vitamin C were determined during the thermal processing of peas canned in 303 x 4OC cans. The Dz50 values for loss of color, firmness, and vitamin C were 13.2 min, 9.2 min, and 246 min, respectively. The corresponding z values were: 69"F, 66"F, and 91"F, respectively. These :esults are in good agreement with those reported in the litera.ure. With proper precautions and corrections for lags, kinetic par;!meters for the loss of quality parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 0 publications
8
33
1
1
Order By: Relevance
“…This result exhibited that low temperature processing brought about minor effect on the drop of AA content, however, high temperature treatment led to tremendous decrease in the content of AA. This is somehow consistent with the previous reports (Burg & Fraile, 1995;Dewanto et al, 2002;Lathrop & Leung, 1980;Murcia et al, 2000;Rao et al, 1981). Gregory (1996) proposed that the loss of AA was primarily due to chemical degradation involving oxidation of ascorbic acid to dehydroascorbic acid, followed by hydrolysis to 2,3-diketogulonic acid and further polymerization to form other nutritionally inactive products.…”
Section: Quantitative Analysis Of Antioxidative Componentssupporting
confidence: 86%
See 1 more Smart Citation
“…This result exhibited that low temperature processing brought about minor effect on the drop of AA content, however, high temperature treatment led to tremendous decrease in the content of AA. This is somehow consistent with the previous reports (Burg & Fraile, 1995;Dewanto et al, 2002;Lathrop & Leung, 1980;Murcia et al, 2000;Rao et al, 1981). Gregory (1996) proposed that the loss of AA was primarily due to chemical degradation involving oxidation of ascorbic acid to dehydroascorbic acid, followed by hydrolysis to 2,3-diketogulonic acid and further polymerization to form other nutritionally inactive products.…”
Section: Quantitative Analysis Of Antioxidative Componentssupporting
confidence: 86%
“…Generally, processed products have been considered to have lower nutritional value than their respective fresh commodities mainly due to the loss of nutritional compounds such as vitamin during processing (Burg & Fraile, 1995;Lathrop & Leung, 1980;Murcia, Lopez-Ayerra, Martinez-Tome, Vera, & Garcia-Carmona, 2000;Rao, Lee, Katz, & Cooley, 1981). However, Stahl and Sies (1992) suggested that a greater content of lycopene was found in heat-processed tomato juice than that in unprocessed one.…”
Section: Introductionmentioning
confidence: 92%
“…With reference to kinetics of destruction of vitamin C in food systems, different buffer systems and real products with different processing methods have been examined (Frias, Oliveira, Cunha, & Oliveira, 1998;Hussein et al, 2000;Lathrop & Leung, 1980;Lee & Nagy, 1988;Lima, 1997;Lima, Heskitt, Burianek, Nokes, & Sastry, 1999;Rao, Lee, Katz, & Cooley, 1981;Robertson & Samaniego, 1986;van den Broeck, Ludikhuyze, Weemaes, Loey, & Hendrickx, 1998). Many of these studies are related to the storage of pasteurized juices or higher temperatures of processing.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods have been developed to determine the texture, but data are frequently incomparable between laboratories due to the lack of standardisation. The incidence of heat treatment on the texture has been studied for various vegetables (Leung, Barron, & Davis, 1983;Rao, Lee, Katz, & Cooley, 1981). The mechanical properties are significantly affected by the mode of cooking (Cheng & Sun, 2004;Xie, Xiong, & Church, 1998).…”
Section: Introductionmentioning
confidence: 99%